Extra-virgin olive oil production sustainability in northern Italy: a preliminary study. Issue 12 (25th November 2014) - Menozzi, Davide
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Sustainability of the origin-based production and promotion system of a geographical indication (GI) depends on the remuneration from the market and the local resources reproduction. The purpose of this paper is to evaluate the sustainability and the development of olive growing and extra-virgin olive oil production in the Emilia Provinces (northern Italy) using the origin-based quality virtuous circle as a conceptual framework. Design/methodology/approach – In total, 11 personal interviews and one focus group with six olive producers were conducted to assess the product potential and the willingness to set up rules for value creation and preservation of local resources. A survey of 100 extra-virgin olive oil consumers was performed to examine the product perception and consumers' willingness to pay. Findings – The origin-based quality virtuous circle was used as a conceptual framework to deal with the different aspects involved in the development and sustainability of the GI system. The results show that the value creation and preservation process of extra-virgin olive oil production in the Emilia Provinces has good potential, although many problems still exist, such as a lack of technical and agronomic expertise, and the lack of organisation among the producers. These weaknesses should be addressed to enhance the potential for sustainable development of the GI system. Practical implications – The creation of a GI organisation, such as a Consortium, may play a central role in coordinating collective action, such as providing technical assistance, managing the internal rules and controls system along the supply chain, and the marketing and communication strategies. Social implications – The future development of olive production, by reducing the risk of land abandonment, would contribute to landscape protection and improvement of the geological structure of the Emilia hilly areas, which are under serious threat of soil erosion and landslide events. Originality/value – This study represents the first attempt to evaluate the economic and development potential of olive growing and extra-virgin olive oil production in non-specialised areas, using the origin-based quality virtuous circle as a conceptual framework.